(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper deals with the concepts of weakly β(Λ, p)-open functions and weakly β(Λ, p)-closed functions. Moreover, some properties of weakly β(Λ, p)-open functions and weakly β(Λ, p)-closed functions are investigated.